Effects of connectors on the heat transfer coefficient of reinforced composite rock wool board insulation system and optimization of combined mechanical properties. (1st June 2023) - Luo, Zhixing; Zhang, Shuaishuai; Zhang, Linman; Hu, Xinyue; Huang, Peizeng; Tang, Wenjian; Wang, Haining
Highlights: Propose a calculate method to evaluate the effect of connector on U-value. Anchor bolts had a more effect on U-value of insulation system than steel wire mesh. The effect of connector on U-value change regularly anchor bolts. The effect of connector on U-value change regularly thickness of rock wool board. Propose a solution to reduce the effect of connector on U-value. Abstract: Insulation system is an important method to improve the thermal performance of the building envelope. The use of metal connections in the insulation system improves the mechanical properties of the insulation system but reduces its thermal performance. Firstly, in this paper, the effects of connectors (steel anchor bolts and steel wire mesh) on the heat transfer coefficient of the insulation system are studied by finite element simulation method with the reinforced composite rock wool board insulation system as an example. The feasibility of this method was verified by the guarded hot box method. The results show that using connectors harms the insulation system's heat transfer coefficient, with steel anchors having a more significant effect than wire mesh. Then, an optimization scheme to reduce this adverse effect is proposed while satisfying the mechanical properties (gravity load and wind load) of the insulation system. When the thickness of the rock wool board in the insulation system is 70 mm, 100 mm, and 140 mm, the effects of the connectors on the heat transfer coefficient of the insulation system is reduced by 7.3%, 5.8%, and 4.9%, respectively, after using the optimized scheme. This study provides an informed decision on calculating the thermal performance of the envelope structure. It has important implications for reducing building energy consumption and promoting the application of this new type of insulation system in energy-efficient buildings.